KESEJAHTERAAN LANSIA DAN BEBERAPA FAKTOR YANG MEMPENGARUHI DI DESA DANGIN PURI KAUH - Raka Riani Tanaya; I Gusti Wayan Murjana Yasa (PIRAMIDA, 2015)
Indicators of success of development is the increasing life expectancy of the population. The purpose of this studywas to determine the effect of religiosity , economic conditions , and access to health simultaneously and partiallyto the welfare of the elderly in Dangin Puri Kauh . Then the sample was taken 86 of the total 624 elderly seniorswho are in Dangin Puri Kauh . This study used quantitative analysis techniques namely multiple linear regressionanalysis . Based on the results of the study , obtained information that Religiosity ( X1 ) , Economics ( X2 ) , andHealth ( X3 ) , has a significant effect simultaneously and partially on the elderly Welfare ( Y ) on Dangin Puri Kauh. This means that the higher the religiosity ( X1 ) , Economics ( X2 ) , and Health ( X3 ) owned by the elderly , theelderly Welfare Kauh Dangin Puri Denpasar will increase .